2006
DOI: 10.1080/07357900601062339
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Administration of Mifepristone (RU486): Clinical Tolerance During Extended Treatment of Meningioma

Abstract: Long-term administration of mifepristone is feasible and clinically well tolerated, with generally mild toxicity. However, endometrial hyperplasia was noted in several patients. In view of the association between long-term treatment with tamoxifen (another agent that can induce an unopposed estrogen effect) and endometrial cancer, this observation will require further investigation and screening. Minor regression of meningioma that can result in significant clinical benefit is suggested in the male and premeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(107 citation statements)
references
References 39 publications
(32 reference statements)
0
105
0
2
Order By: Relevance
“…20 Mifepristone (RU-486), a progesterone receptor antagonist, generated some excitement when early small-scale studies suggested a potential therapeutic benefit, but this was largely refuted by a multicenter randomized Phase III clinical trial in which 180 patients were enrolled, which failed to show any major clinical benefit. 19,21 A major limitation of this study, aside from a small sample size and heterogeneous pretrial treatment histories (that is, prior surgery, radiosurgery, and so on), was that progesterone receptor expression is often not retained in the setting of tumor progression and malignant transformation of meningiomas, and most patients recruited in this trial had more aggressive meningioma subtypes. 79 Tamoxifen, an estrogen receptor antagonist, was also investigated as a possible candidate drug.…”
Section: Hormonal Agentsmentioning
confidence: 99%
“…20 Mifepristone (RU-486), a progesterone receptor antagonist, generated some excitement when early small-scale studies suggested a potential therapeutic benefit, but this was largely refuted by a multicenter randomized Phase III clinical trial in which 180 patients were enrolled, which failed to show any major clinical benefit. 19,21 A major limitation of this study, aside from a small sample size and heterogeneous pretrial treatment histories (that is, prior surgery, radiosurgery, and so on), was that progesterone receptor expression is often not retained in the setting of tumor progression and malignant transformation of meningiomas, and most patients recruited in this trial had more aggressive meningioma subtypes. 79 Tamoxifen, an estrogen receptor antagonist, was also investigated as a possible candidate drug.…”
Section: Hormonal Agentsmentioning
confidence: 99%
“…However, endometrial hyperplasia was noted in several patients (nZ3) and one patient developed peritoneal adenocarcinoma after 9 years of therapy. Minor responses (improved automated visual field examination or improved CT or MRI scan) were noted in eight patients, seven of whom were male or premenopausal female, which can result in significant clinical benefit in this subgroup of patients (Grunberg et al 2006). The only prospective study on this topic was conducted on 160 patients.…”
Section: Chargari Et Al: Endocrine Therapy In Meningioma Managementmentioning
confidence: 99%
“…Mifepristone's lack of efficacy may be explained in part by the loss of progesterone receptor expression in meningiomas with increased proliferation index and histologic grade. This is relevant because these advanced tumors are the type most likely to be enrolled into clinical studies (Grunberg et al, 2006;Wen et al, 2010).…”
Section: Progesterone Receptor Inhibitionmentioning
confidence: 99%
“…A study following 28 patients with unresectable meningiomas treated with mifepristone for median duration of 35 months (Grunberg et al, 2006) has shown minor responses in 8 patients, 7 of whom were male or premenopausal female. The most common side effects were fatigue, hot flashes and gynecomastia/breast tenderness.…”
Section: Progesterone Receptor Inhibitionmentioning
confidence: 99%